REHABILITATION OF CHILDREN WITH DISMETABOLIC NEPHROPATHIES, LIVING IN INDUSTRIAL CITIES - K.E. Kazakova; E.I. Kondrat'eva; A.A. Terent'eva; G.A. Sukhanova ("Paediatrician" Publishers LLC, 2009)
This article presents results of nephrological and urological diagnostics and treatment of 48 children with dismethabolic nephropathy in age 2-15 years old. Oxalaturia was diagnosed in 75% of patients, uraturia - in 25%, isolated crystaluria - in 47,5%, combination with microeritrocyturia and (or) proteinuria - 52,5%. Besides, increasing of malonic dialdehyde concentration in blood and urine, protein, beta2-microglobulin and nitrites in blood and urine was marked. This fact testifies to instability of cell membranes and presence of disorders of kidney tissue function. Use of Caneohron N in rehabilitation of children with dismethabolic nephropathies in mono- or combined treatment course leads to normalization of level of malonic dialdehyde, nitric oxide, proteinuria and beta2-microglobulin.Key words: children, dismetabolic nephropathy, treatment, rehabilitation.(Voprosy sovremennoi pediatrii - Current Pediatrics. 2009;8(1):41-45)